Political Failures in Innovation Policy: A Cautionary Note - Anders Kärnä; Johan Karlsson; Erik Engberg (Research Institute of Industrial Economics (IFN), 2020)
Within the field of innovation studies, researchers have identified several market failures that hamper investment in R&D, innovation and growth in a market economy. Several policies such as government subsidies, tax deductions, soft loans, and public venture capital provided to firms that pursue R&D have therefore been recommended by researchers, in addition to regulations to increase the quality and standards of goods and services. Less attention has been paid to government failures in cases where a policy fails to achieve its stated goal, often due to conflicts between the interests of special interest groups and the public. This paper discusses the concept of government failure within an innovation policy context and why this perspective is important for policy design since it is likely that policies that aim to reduce market failures could suffer from political failures. A text analysis of all papers published in 5 leading innovation journals between 2010 and 2019, a total of 5,526 papers, indicates a lack of research about government failures, which could lead to recommendations from researches to policymakers not being successful due to political failures.
Keywords: L52; O38; H81; L26; G28; P16; 330; Innovation policy; Political economy; Political failure; Market failure; Public choice